Penyuluhan Gizi Seimbang Anak TK Di Desa Sei Suka Deras serta Pengukuran Antropometri : Kolaborasi Puskesmas dan Mahasiswa KKN. - Sofi Inayah; Mardatilla Riadi; Maulida Sahrani; Nadiya Sofiadi; Leyli Rahmadani; Rahmadani (LPPI UMN AL WASHLIYAH, 2026)
Adequate nutrition plays a crucial role in supporting the growth and overall development of children in early childhood. Nutrients serve as essential components required by the body, particularly in promoting physical development, maintaining a healthy nervous system, enhancing brain function, shaping intelligence, and improving children’s intellectual abilities. Sufficient and balanced nutritional intake is an important prerequisite to ensure that children can grow and develop optimally according to their genetic potential. Moreover, fulfilling nutritional needs from an early age provides a strong foundation for long-term health, strengthens the immune system, and reduces the risk of nutritional problems and diseases in the future. This community service activity aims to detect early nutritional status problems in preschool children while providing education regarding the importance of consuming nutritious food. The methods used include health education on balanced diet through the balanced nutrition pyramid and nutritional status screening using anthropometric measurements. These measurements were carried out by assessing height, weight, Body Mass Index for age, as well as calculating the z-score. The results showed that out of 23 children examined, 74% or 17 children had normal nutritional status. This finding emphasizes the importance of regular nutrition monitoring, as the preschool years are a period of rapid growth. Visual education using the balanced nutrition pyramid is expected to help children recognize healthy foods, prevent malnutrition, and support optimal growth and development.